Assessment of hydration status by urinary analysis of elite junior taekwon-do athletes in preparing for competition - Kutlu, Mehmet; Guler, Gokcen (Taylor & Francis Ltd, 2006)
The aim of this study was to assess over time the hydration status of taekwon-do athletes during a preparatory camp. Measures of urine osmolality, conductivity, specific gravity and colour were made on the first urine sample passed by the participants (n = 32) in the morning before breakfast. The urinary measurements were made on samples collected at the beginning of the camp, 5 days later and one day before competition. Body mass was also measured at the same instants. Body mass (mean +/- s) was essentially the same on each of the measurement days (62.6 +/- 12.2, 62.7 +/- 12.3 and 62.2 +/- 12.6 kg, respectively). Mean urine osmolality at the beginning of the camp was relatively high (998 +/- 171 mOsmol . kg(-1)), suggesting that a significant number of the athletes were already hypohydrated. However, no significant differences were detected in urine osmolality at the three time points during the study. There were no significant differences in any of the four methods of urine analysis during the study (P > 0.05). The average values for all samples were 989 +/- 205 mOsmol . kg(-1) for osmolality, 25.5 +/- 6.7 mS . cm(-1) for conductivity, 1.017 +/- 0.010g . cm(-3) for specific gravity and 4 +/- 1 arbitrary units for colour. Correlation analysis between the different methods suggested moderately good agreement (correlation coefficient = 0.5-0.7) between all four measurement techniques (P +/- 0.01). The coefficients of variation for these techniques were relatively low (CV = 11.8 - 35.0%). The results of this study suggest that some of the taekwon-do athletes were slightly hypohydrated in the morning on each of the test days, but there was no evidence to suggest that most of the athletes further restricted their fluid intake to make weight. In addition, it appears that each of the four methods used gave essentially the same estimate of hydration status of these athletes.
Keywords: dehydration; urinary measures; taekwon-do athletes